Contextual citizenship in modern Islamic thought - Scott, Rachel M. (Islam and Christian-Muslim relations, 2007)
This paper examines the concept of citizenship in Egyptian Islamic thought. It focuses on a group of intellectuals referred to as the ‘New Islamists’, who have articulated a kind of Islamic citizenship which would include non-Muslim minorities. In contrast to many Islamists, these thinkers do not advocate reviving the dhimma as a model for the treatment of non-Muslims within an Islamic state. The paper looks at the methods and arguments used for justifying citizenship within the Islamic ideological framework. It compares this conception of citizenship with Western assumptions and shows that there are a number of divergences. However, it also questions the efficacy of simply judging citizenship in Islamic thought through this lens. It asks whether a more constructive question is whether Egyptian Islamists have been able to articulate a conception of citizenship that has evolved ‘contextually’, taking into account Egyptian social, moral, and political culture.